2014
DOI: 10.1371/journal.pone.0104127
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of Luteal Transcriptome during Prostaglandin F2-Alpha Treatment in Buffalo Cows: Analysis of Signaling Pathways Associated with Luteolysis

Abstract: In several species including the buffalo cow, prostaglandin (PG) F2α is the key molecule responsible for regression of corpus luteum (CL). Experiments were carried out to characterize gene expression changes in the CL tissue at various time points after administration of luteolytic dose of PGF2α in buffalo cows. Circulating progesterone levels decreased within 1 h of PGF2α treatment and evidence of apoptosis was demonstrable at 18 h post treatment. Microarray analysis indicated expression changes in several of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 126 publications
(148 reference statements)
6
30
0
1
Order By: Relevance
“…In this study, large changes in chemokine mRNA in the CL of pregnancy were noted, particularly a morethan 10-fold decrease in lymphotactin, a chemokine that recruits T cells, and a more-than 100-fold increase in eotaxin, a chemokine that recruits eosinophils. This study also noted a more modest increase in growth factor-related mRNA during early pregnancy (Sakumoto et al, 2015). Similarly, a microarray study performed by Romero et al (2013) demonstrated that in the ovine CL of early pregnancy, there is stabilization or upregulation of pathways related to interferon and cytokine signaling, cell-cell adhesion, and cytoskeleton, as compared to the late and regressing CL.…”
Section: Transcriptomic Profiling In the Corpus Luteumsupporting
confidence: 70%
See 1 more Smart Citation
“…In this study, large changes in chemokine mRNA in the CL of pregnancy were noted, particularly a morethan 10-fold decrease in lymphotactin, a chemokine that recruits T cells, and a more-than 100-fold increase in eotaxin, a chemokine that recruits eosinophils. This study also noted a more modest increase in growth factor-related mRNA during early pregnancy (Sakumoto et al, 2015). Similarly, a microarray study performed by Romero et al (2013) demonstrated that in the ovine CL of early pregnancy, there is stabilization or upregulation of pathways related to interferon and cytokine signaling, cell-cell adhesion, and cytoskeleton, as compared to the late and regressing CL.…”
Section: Transcriptomic Profiling In the Corpus Luteumsupporting
confidence: 70%
“…Little is known about changes that occur within the CL to facilitate its rescue during early pregnancy. When the CL of pregnancy was compared to midcycle (days 10-12) CL, differentially abundant mRNA gradually increased throughout pregnancy (Sakumoto et al, 2015), indicating that, once rescued, the CL is not static, but is actively regulated by either intrinsic or extrinsic factors that alter mRNA abundance to facilitate luteal survival and progesterone production. In this study, large changes in chemokine mRNA in the CL of pregnancy were noted, particularly a morethan 10-fold decrease in lymphotactin, a chemokine that recruits T cells, and a more-than 100-fold increase in eotaxin, a chemokine that recruits eosinophils.…”
Section: Transcriptomic Profiling In the Corpus Luteummentioning
confidence: 99%
“…Accordingly, there is likely time-dependent secretion of cytokines to recruit and activate the various leukocytes (Townson and Liptak, 2003). Several cytokine transcripts are induced by PGF2a in the mid-to late-stage CL including tumor necrosis factor alpha (TNF) (Shah et al, 2014), interleukin 1 beta (IL1B) (Atli et al, 2012;Mondal et al, 2011), TGFB1 (Hou et al, 2008;Mondal et al, 2011;Shah et al, 2014), and the chemokines; C-C motif chemokine ligand 2 (CCL2, previously known as MCP1) (Mondal et al, 2011;Penny et al, 1998) and C-X-C motif 8 (CXCL8, previously known as IL8) (Atli et al, 2012;Mondal et al, 2011;Shah et al, 2014;Shirasuna et al, 2012b;Talbott et al, 2014). These cytokines have pleiotropic effects on luteal cells, including inhibition of progesterone secretion, stimulation of PGF2a secretion, and stimulation of apoptosis of multiple luteal cell types (Pate et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this study was to understand the early PGF2aelicited changes in the CL based on temporal patterns of early transcript expression following in vivo treatment with PGF2a. While many studies have examined luteolytic alterations both in vivo and in vitro, most studies have focused on changes 3e24 h after PGF2a administration (Mondal et al, 2011;Shah et al, 2014) or used targeted rather than global approaches (Atli et al, 2012;Shirasuna et al, 2012aShirasuna et al, , 2010. Therefore, little is known about the very early temporal changes in global mRNA expression elicited in response to PGF2a treatment in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Behavioural oestrus was characterized by an increase of cervical mucus production, as well as by the lack of reflex reaction to the pressure in the pelvic region by the examiner (Curlewis et al, 1988;Zanetti et al, 2010) or when remaining still while the male attempted to court and mount her. After the first natural oestrus of a female, we normally induced subsequent cycles by applying 265 g cloprostenol (1 mL Ciosin; Schering Plough Coopers, Brazil), a synthetic analogues of prostaglandin F2 alpha to provoke the regression of corpora lutea and restart the oestrus cycle (Shah et al, 2014).…”
Section: Manipulation Of Animals and Conducting Mating Trialsmentioning
confidence: 99%